MAKNA COMPANG DALAM PERSPEKTIF MASYARAKAT SUKU WATU BARU DI DESA WATU BARU KECAMATAN MACANG PACAR KABUPATEN MANGGARAI BARAT - Wilfridus Parli; Syarifudin Darajad; Amir Syarifudin Kiwang (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2019)
Compang is a place of ceremony for the Manggarai community which was built in the middle of the village. marked by banyan tree planting and flat stone as a place of ceremony. Every year society often perform a ceremony there. Compang's existence as place of worship of the people to the spirits of the ancestors and also as a place giving offerings has meaning and very important meaning for the Manggarai community. Therefore the writer is interested in research this. The problems of this research are : What is the meaning of Compang for the Watu Baru tribe community. The purpose of this research is to find out: (1) History of the existence of the Compang Watu Baru, (2) Describe the tradition of compang in the Watu Baru tribal community, and (3) To find out the meaning of compang for the people of the Watu Baru tribe. The method used is a descriptive qualitative research. The location of the study was in Watu Baru Village, Macang Pacar Subdistrict, West Manggarai Regency, the technique of determining informants using purposive sampling technique, the data analysis technique used was descriptive qualitative. Research results show (1) that Compang has a very important meaning in the life cycle of the Manggarai people. In Compang the dwelling place of the naga golo / naga beo (village spirit). This naga golo /naga beo becomes the guardian and protector of the village from various things. Specifically all the doom and disaster that befell the village. Compang is also a sacred site through which villages get a fortune in life. At each penti weki peso (annual communal thanksgiving ceremony), at Compang, thanksgiving is given to the guardians and protectors of the village, the ancestors and the Creator. Compang is also a source of strength. Every villager wants to go to the battle area (raha rumbu tana, rampas), the war perpetrators surround Compang seven times. In large rites, such as opening the Uma weru (new communal garden), building a new traditional house (pande mbaru gendang weru), Roko Molas Poco (taking the main pillar of mendang drum from the forest), the traditional elders guarded it with takung (offerings) in Compang to ask for your blessing and at the same time beg for the success of the event. AbstrakCompang merupakan tempat upacara bagi masyarakat Manggarai yang dibangun ditengah kampung, ditandai dengan adanya penanaman pohon beringin dan batu ceper sebagai tempat upacara. Setiap tahun masyarakat sering melakuakan upacara disana. Keberadaan Compang sebagai tempat pemujaan masyarakat kepada roh nenek moyang dan juga sebagai tempat pemberian sesaji memiliki makna dan arti yang sangat penting bagi masyarakat Manggarai. Oleh karenanya penulis tertarik untuk meneliti hal ini. Permasalahan penelitian ini adalah Bagaimana makna Compang bagi masyarakat suku Watu Baru. Tujuan penelitia ini untuk mengetahui:(1) Sejarah keberadaan Compang Watu baru,(2) Mendeskripsikan tradisi compang pada masyarakat suku Watu Baru, dan (3) Untuk mengetahui makna compang bagi masyarakat suku Watu Baru. Metode yang digunakan adalah metode penelitian deskriptif kualitatif. Lokasi penelitian di Desa Watu Baru kecamatan Macang Pacar kabupaten Manggarai Barat, teknik penentuan informan dengan menggunakan teknik purposive sampling, Teknik analisis data yang digunakan adalah deskriptif kualitatif. Hasil Penelitian menunjukan (1) bahwa Compang memiliki arti yang sangat penting dalam siklus kehidupan orang Manggarai. Di Companglah tempat tinggal dari naga golo/naga beo (roh kampung). Naga golo/beo ini menjadi penjaga dan pelindung kampung dari berbagai hal. Khususnya segala malapetaka dan bala yang menimpa kampung. Compang juga menjadi situs sakral yang melaluinya kampung mendapat rejeki kehidupan. Di setiap penti weki peso (upacara syukur tahunan secara komunal), di Compang dipersembahkan syukuran kepada penjaga dan pelindung kampung, para leluhur serta Sang Pencipta. Compang juga menjadi sumber kekuatan. Disetiap warga kampung hendak pergi ke area pertempuran (raha rumbu tanah, rampas), para pelaku perang mengelilingi Compang tujuh kali. Dalam ritus-ritus besar, semisal membuka lingko weru (kebun komunal baru), membangun rumah adat baru (pande mbaru gendang weru), Roko Molas Poco (pengambilan tiang utama mbaru gendang dari hutan), tetua adat mengawalinya dengan takung (persembahan) di Compang untuk meminta restu sekaligus mohon kesuksesan dari acara dimaksud.